A choice of weapons - Parks, Gordon 1912-2006 (Harper & Row, 1973)
With love, dignity and hard work Life-photographer Gordon Parks wins his battle against the debasement of poverty and racial discrimination.
Keywords: Parks, Gordon <1912-2006>; Parks, Gordon -- 1912-2006; Geschichte 1900-2000; African American photographers -- United States -- Biography; Authors, American -- 20th century -- Biography; Autobiografie; USA; Biografie